Why the Great Food Transformation may not happen – A deep-dive into our food systems’ political economy, controversies and politics of evidence - Béné, Christophe (Elsevier, 2022)
This paper explores the conditions under which the changes leading to the Great Transformation of food systems called upon by a growing number of international experts and development agencies, will (or not) happen. After discussing the meanings of ‘transformation’ in the specific context of food systems, we draw on different elements of political economy to show how various self-reinforcing dynamics are contributing to lock food systems in their current unsustainable trajectories. Those include the concentration of economic and market power in the hands of the Big Food transnational corporations but also other actors’ ideology, policy incoherence, national interests or culturally-embedded aspirations, which together create irreconcilable trade-offs and tensions between divergent individual and societal objectives and prevent the system from aligning toward a more sustainable trajectory. In this context, while innovation is often presented as a ‘game-changer’, we show how the current profit-driven nature of its evolutionary selection creates a random, adirectional, process incapable of steering food systems towards sustainability. We argue that unless those different issues are tackled all together in a resolutely normative, global, and prescriptive manner in which science would have a new role to play, there are serious risks that the Great Transformation will not happen. Based on these analyses, we identify pathways to move the systems past its current locks-in and steer it toward its long-awaited sustainable transformation. In doing so we demonstrate that what is needed is not just a transformation of the food systems themselves, but a transformation of the governance of those food systems as well.